Morphogenetic transformations of the upper jaw rudiment and the structures of the maxillofacial region in human pre-fetuses aged 10-12 weeks of prenatal ontogenesis. - Oshurko, A. P.; Oliinyk, I. Yu. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Based on the study of scientific literature, the authors concluded that the upper jaw in the perinatal period of ontogenesis is characterized by the diversity of the topical position of its processes and walls and predetermines the need for further anatomical studies of its prenatal ontogenesis. Having completed the first stage of the work, we considered it expedient to continue the study of the features of morphogenesis of the maxillofacial region in the dynamics of the pre-fetal period of human ontogenesis in the 10th -12th weeks of fetal developmentas a prospect of further researches. Objective. To study the features of the morphogenesis of the upper jaw and some structures of the human maxillofacial region in the dynamics of the 10th - 12th weeks of the prenatal ontogenesis. Material and methods. The study was conducted on 21 specimens of human pre-fetuses with 42.2-79.0 mm of crown-rump length (10-12 weeks of intrauterine development) using the methods of macroscopy, morphometry, manufacturing and microscopy of a series of sequential histological sections of human embryonic specimens and that of histochemistry. Results. During the 10th week of the intrauterine development (IUG), one can clearly identify the newly formed branches of the mandible, formed by the hyaline cartilaginous tissue, in the structure of the human maxillofacial region. In the histogenetically modeled bony basis of the mandible it is possible to recognize the alveolar grooves well-filled with mesenchyma cells as well as blood vessels and nerves. The bone plates, forming the alveolar grooves, open towards the side of the tooth buds. During the 11-12th weeks of the human IUG a complete separation of the oral and nasal cavities is finished, there is a further formation of the oral cavity vestibule, morphological transformations in the hard and soft tissues of the organs and structures of the maxillofacial region continue to increase due to the establishment of reciprocal relationships between the various tissue rudiments, therefore, it can be argued that there is a formed bony basis of the upper and lower jaws; their surrounding connective tissue structures and chewing muscles differentiate rapidly. Conclusion. Based on the study of the histogenesis features of the maxillofacial region in the embryonic [15] and pre-fetal periods of prenatal ontogenesis, one can conclude that on the completion of the 12th week of human IUG there are all prerequisites for an in-depth study to find out the features of the structure (density) and mineral composition of bone tissue of the human upper jaw in the dynamics of the fetal period of the prenatal ontogenesis.